Soil properties as key predictors of global grassland production: Have we overlooked micronutrients?. (6th October 2021) - Radujković, Dajana; Verbruggen, Erik; Seabloom, Eric W.; Bahn, Michael; Biederman, Lori A.; Borer, Elizabeth T.; Boughton, Elizabeth H.; Catford, Jane A.; Campioli, Matteo; Donohue, Ian; Ebeling, Anne; Eskelinen, Anu; et al.
Abstract: Fertilisation experiments have demonstrated that nutrient availability is a key determinant of biomass production and carbon sequestration in grasslands. However, the influence of nutrients in explaining spatial variation in grassland biomass production has rarely been assessed. Using a global dataset comprising 72 sites on six continents, we investigated which of 16 soil factors that shape nutrient availability associate most strongly with variation in grassland aboveground biomass. Climate and N deposition were also considered. Based on theory‐driven structural equation modelling, we found that soil micronutrients (particularly Zn and Fe) were important predictors of biomass and, together with soil physicochemical properties and C:N, they explained more unique variation (32%) than climate and N deposition (24%). However, the association between micronutrients and biomass was absent in grasslands limited by NP. These results highlight soil properties as key predictors of global grassland biomass production and point to serial co‐limitation by NP and micronutrients. Abstract : Using a dataset comprising 72 sites on six continents, we show that of 16 investigated soil factors determining nutrient availability, soil physicochemical properties, C:N and micronutrients are the strongest predictors of the variation in grassland aboveground biomass. Our results highlight soil properties as key predictors of global grassland biomass production and point to the potential importance of micronutrients as co‐limiting factors in grasslands.